Functional training handbook - Liebenson, Craig (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
"Training has many different connotations depending on one's perspective. Traditionally, for healthy individuals or athletes it focused on strength, flexibility, or cardiovascular training. Such training would normally be supervised by a personal fitness trainer or strength and conditioning (S&C) coach . This book promotes a different approach in that the aim of training is to promote athletic development (1,2). From the perspective of sustainable athletic development, training is not limited to strength, flexibility or cardiovascular domains, but also focuses on the fundamental A,B,Cs of agility, balance, and coordination as a foundation for enhanced movement literacy (3)"--